2021
DOI: 10.3390/en14175485
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Mixed Convective Heat Transfer from a Square Cylinder Utilizing Nanofluids with Multi-Phase Modelling Approach

Abstract: The present study deals with the numerical simulation of mixed convective heat transfer from an unconfined heated square cylinder using nanofluids (Al2O3-water) for Reynolds number (Re) 10–150, Richardson number (Ri) 0–1, and nanoparticles volume fractions (φ) 0–5%. Two-phase modelling approach (i.e., Eulerian-mixture model) is adopted to analyze the flow and heat transfer characteristics of nanofluids. A square cylinder with a constant temperature higher than that of the ambient is exposed to a uniform flow. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The present study [35] deals with the numerical simulation of mixed convective heat transfer from an unconfined heated square cylinder using nanofluids (Al2O3-water) for Reynolds number (Re) 10-150, Richardson number (Ri) 0-1, and nanoparticles volume fractions (φ) 0-5%. Minor variations in flow and thermal characteristics are observed between the two approaches for the range of nanoparticle volume fractions considered.…”
Section: Cluster 6 Numerical Flow Modeling Issuesmentioning
confidence: 99%
“…The present study [35] deals with the numerical simulation of mixed convective heat transfer from an unconfined heated square cylinder using nanofluids (Al2O3-water) for Reynolds number (Re) 10-150, Richardson number (Ri) 0-1, and nanoparticles volume fractions (φ) 0-5%. Minor variations in flow and thermal characteristics are observed between the two approaches for the range of nanoparticle volume fractions considered.…”
Section: Cluster 6 Numerical Flow Modeling Issuesmentioning
confidence: 99%
“…Research on nanofluids has shown great potential for optimizing heat transfer behavior in mixed convection systems within ventilated cavities. By studying the effect of nanoparticle density and comparing the performance of nanofluids with that of pure water with respect to heat transfer properties, it has been shown that nanofluids represent a promising means of enhancing heat transfer efficiency in engineering applications [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%